EXPERIMENTAL METHODOLOGY FOR THE STUDY OF NATURAL CONVECTION ON FLAT AND CORRUGATED PLATES - Verdério Júnior, S. A.; Scalon, V. L.; Oliveira, S. R.; Avallone, E.; Mioralli, P. C.; Gonçalves, D. M. (Revista de Engenharia Térmica, 2022)
Natural convection is present in the most different Thermal Engineering systems, such as solar collectors, electric furnaces, electronic equipment cooling, lubrication, thermal comfort projects in buildings, etc. In the last decade, the number of research on natural convection heat transfer has increased considerably, especially in the areas of physical-numerical modeling and validation, experimental construction and efficiency optimization of thermal systems, and related technologies. This work presents an experimental methodology for studying natural convection on flat and corrugated plates. The design and construction stages of the experimental apparatus, data processing and analysis, physical-mathematical modeling and uncertainty analysis were extensively explored. The applications and extensions of the proposed methodology were discussed in the numerical-experimental validation of physical-numerical modeling methodologies, design and optimization of the experimental apparatus and also of measuring instruments and, finally, in sensitivity analysis studies to reduce the propagation of uncertainties. The limitations of the proposed methodology were discussed, pointing out suggestions for future work.